Analisis Metode Penilaian Kinerja Sumber Daya Manusia (Sebuah Gambaran Sederhana Melalui Literatur Review) - Alamsyah Alamsyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Human resource performance is a target achievement in an organization. As a form of evaluation, it is necessary to assess the achievements and planning of human resources. This is done to find out the problems in the HR field faced in an organization. In general, there are nine methods for assessing HR performance. However, not all organizations implement this method, because it is associated with costs and time. The purpose of this research is to analyze and determine the performance assessment methods commonly used by various organizations. Qualitative research method with literature reviews from several journals. The research results show that the HR performance assessment methods carried out by various organizations predominantly use the ABC method.